Pentingnya Pendidikan Empati Untuk Mengurangi Kasus Bullying Di Sekolah Dasar - Lulu Rahma Aulia; Nur Kholisoh; Vadila Zikra Rahma; Deti Rostika; Ranu Sudarmansyah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Bullying, especially in the digital era, has become a serious concern due to its involvement in various forms of physical, verbal, and social violence. Empathy education is considered an integral solution to address this issue by instilling the ability to sense and understand the feelings of others from an early age. This article also outlines the concept of bullying, its effects on perpetrators and victims, as well as its long-term impacts. Furthermore, empathy education is discussed in-depth as a preventive and remedial strategy for bullying. Empathy is not only taught to children but is also applied to those responsible within the school. Through theoretical studies, this article correlates the concept of bullying with a lack of empathy and details the significance of empathy education in the development of students' characters. Empathy education is deemed essential as it influences positive behavior, enhances the quality of social interactions, and fosters meaningful relationships.